Interleukin-18 and Hematopoietic Recovery after Allogeneic Stem Cell Transplantation - Radujkovic, Aleksandar (Cancers (Basel), 2020)
SIMPLE SUMMARY: We have previously shown that high pre-conditioning levels of Interleukin-18 were associated with worse survival after allogeneic stem cell transplantation due to increased non-relapse mortality. While no correlations with acute graft-versus-host disease were observed, interleukin-18-related excess mortality was mainly driven by fatal infectious complications. In multiple studies, delayed hematopoietic recovery and poor graft function following allogeneic stem cell transplantation has been demonstrated as a powerful predictor of non-relapse mortality. The present study links high interleukin-18 to delayed platelet recovery in allografted patients. Given the functions of interleukin-18 in regulating the quiescence of hematopoietic stem/progenitor cells, our findings may be explained by Interferon gamma-independent inhibitory effects of interleukin-18 on stem cell proliferation and hematopoietic reconstitution in allografted patients. Importantly, considering recent successful interleukin-18-neutralizing approaches in autoimmune disorders, our results provide a rationale to explore modulation of interleukin-18 for improving hematopoietic recovery and outcomes in allogeneic stem cell transplantation recipients. ABSTRACT: Interleukin-18 (IL-18) is an immunoregulatory cytokine and a context-dependent regulator of hematopoietic stem/progenitor cell (HSPC) quiescence in murine models. In a previous study, high pre-conditioning levels of IL-18 were associated with increased non-relapse mortality (NRM) after allogeneic stem cell transplantation (alloSCT). To investigate the clinical impact of IL-18 status on hematopoietic function, the associations of pre-conditioning and day 0–3 cytokine levels with platelet and neutrophil recovery were analyzed in a training cohort of 714 allografted patients. In adjusted logistic regression analyses, both increasing pre-conditioning and day 0–3 IL-18 levels had a significantly higher adjusted odds ratio (aOR) of delayed platelet and neutrophil recovery on day +28 post-transplant (aOR per two-fold increase: 1.6–2.0). The adverse impact of high pre-conditioning IL-18 on day +28 platelet recovery was verified in an independent cohort of 673 allografted patients (aOR per two-fold increase: 1.8 and 1.7 for total and free IL-18, respectively). In both cohorts, a platelet count ≤20/nL on day +28 was associated with a significantly increased hazard of NRM (hazard ratio 2.13 and 2.94, respectively). Our findings support the hypothesis that elevated peritransplant IL-18 levels affect post-transplant HSPC function and may provide a rationale to explore modulation of IL-18 for improving alloSCT outcomes.